STUDI JUMLAH TROMBOSIT ANTARA PENDONOR LAKI-LAKI DAN PEREMPUAN PADA USIA YANG BERBEDA DI UNIT TRANSFUSI DARAH CABANG KOTA MALANG - Khasanah, Anis Nur; Suyadi, Suyadi (Jurnal Florea, 2014)
Blood is part of the body which has 6-8 % of total body weight which include of the blood cell and plasma. Thrombocyte is one of component in the blood which has an important function in blood coagulation. This study is aimed to evaluate the influence of the sex and age of donor on the number of thrombocyte. Blood sample were collected at Blood Transfusion Unit of Malang. This research using cases study whose use to observe the number of thrombocyte in man and woman donor at different age. Total of 40 sample (20 of each sex) whose classified as â¤31, 31-40, 41-50 and â¥ 51 years of age. The number of thrombocyte which determined by hemocytometerÂ  Â and observeÂ  under microscopeÂ  Â (magnification:Â  Â 100 ). Â The collected data where analyze by unpaired T-test for man and woman one. While Anova whose use to analyze the differences between ages interval both in the man and woman. Â Duncan test (5%) whose Â use Â toÂ  determine Â the Â significant different between ages group. The Â result Â show Â that Â the Â number Â ofÂ  thrombocyte Â whose Â significantly higher (P<0,05) than those in the woman (245.750 + 76300 vs 201.750 + 61564). The age of donor whose significantly influence on the number of thrombocyte (P<0,05) both in the man and woman. The number of thrombocyte degrees significantly by increasing the age. However for the both sex can donor the blood of more than 51 years of age.Keywords: thrombocyte, man, woman and age.